Forecasting Network Traffic in the Information and Telecommunication System of Railway Transport by Means of a Neural Network - Zhukovytskyy, Igor V.; Pakhomova, Victoria M. (MATEC Web of Conferences, 2023)
ENG: Network traffic is one of the most important actual indicators of the information and telecommunication system (ITS) of railway transport. Recent studies show that network traffic in the ITS of railway transport is self-similar (fractal), for the study of which the Hirst indicator can be used. One of the possible solutions is a method of network traffic forecasting using neural network technology, which will allow you to manage traffic in real time, avoid server overload and improve the quality of services, which confirms the relevance of this topic. The method of forecasting the parameters of network traffic in the ITS of railway transport using neural network technology is proposed: for long-term forecasting (day-ahead) of network traffic volume based on network traffic volumes for the previous three days using the created multilayer neuro-fuzzy network; for short-term prediction (one step forward, which takes five minutes) of network traffic intensity based on network traffic intensities for the previous fifteen minutes using the created multilayer neural network. The corresponding samples are formed on the basis of real values of network traffic parameters in the ITS of railway transport. Studies of optimal parameters of the created multilayer neural network, which can be integrated into specialized analytical servers of the ITS of railway transport, are carried out, which will provide a sufficiently high level of short-term forecasting of network traffic parameters (in particular intensity) in the ITS of railway transport at the stage of deepening the integration of the national transport network into the Trans-European Transport Network.

UKR: Мережевий трафік є одним з найважливіших фактичних показників роботи інформаційно-телекомунікаційної системи (ІТС) залізничного транспорту. Останні дослідження показують, що мережевий трафік в ІТС залізничного транспорту є самоподібним (фрактальним), для дослідження якого може бути використаний показник Херста. Одним із можливих рішень є метод прогнозування мережевого трафіку з використанням нейромережної технології, яка дозволить провести управління трафіком в режимі реального часу, уникнути перевантаження серверів та підвищити якість послуг, що підтверджує актуальність даної теми. Запропонована методика прогнозування параметрів мережевого трафіку в ІТС залізничного транспорту з використанням нейромережної технології: для довгострокового прогнозування (на добу вперед) обсягу мережевого трафіку на основі обсягів мережевого трафіку за попередні три доби з використанням створеної багатошарової нейронечіткої мережі; для короткострокового прогнозування (на крок вперед, у якості якого взято п’ять хвилин) інтенсивності мережевого трафіку на основі інтенсивностей мережевого трафіку за попередні п’ятнадцять хвилин з використанням створеної багатошарової нейронної мережі. Відповідні вибірки сформовані на основі реальних значень параметрів мережевого трафіку в ІТС залізничного транспорту. Проведені дослідження оптимальних параметрів створеної багатошарової нейронної мережі, яка може бути інтегрована в спеціалізовані аналітичні сервери ІТС залізничного транспорту, що забезпечить достатньо високий рівень короткострокового прогнозування параметрів мережевого трафіку (зокрема інтенсивності) в ІТС залізничного транспорту на стадії поглиблення інтеграції національної транспортної мережі в Транс’європейську транспортну мережу.
Прогнозування мережевого трафіку в інформаційно-телекомунікаційній системі залізничного транспорту засобами нейронної мережі
I. Zhukovytskyy: ORCID 0000-0002-3491-5976; V. Pakhomova: ORCID 0000-0002-0022-099X
Keywords: railway transport; ITS; analytical server; forecasting; network traffic; parameter; neural means; error; epoch; залізничний транспорт; сервер; прогнозування; мережевий трафік; параметр; нейронний засіб; похибка; епоха; КЕОМ; TECHNOLOGY::Information technology